2015
DOI: 10.3758/s13423-015-0977-2
|View full text |Cite
|
Sign up to set email alerts
|

Time to see the bigger picture: Individual differences in the attentional blink

Abstract: If two to-be-identified targets are presented in close temporal succession, identification for the second target is typically impaired. This attentional blink (AB) phenomenon has long been considered as a robust, universal cognitive limitation. However, more recent studies have demonstrated that AB task performance greatly differs between individuals, with some individuals even showing no AB in certain paradigms. Several studies have focused on these individual differences in an attempt to reveal the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 111 publications
3
26
0
Order By: Relevance
“…However, the replicability of these findings needs further examination (i.e., see Footnote 1 in Olivers and Nieuwenhuis, 2006, which noted that attempts to replicate the result of listening to music had failed). In addition, introducing an additional task in the RSVP task may result in a more shallow level of stimulus processing (Willems and Martens, 2016). Nevertheless, although it is a widely tested theoretical model that AB occurs because of the temporal limitations of attentional resources, the mechanism of the occurrence of AB still demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the replicability of these findings needs further examination (i.e., see Footnote 1 in Olivers and Nieuwenhuis, 2006, which noted that attempts to replicate the result of listening to music had failed). In addition, introducing an additional task in the RSVP task may result in a more shallow level of stimulus processing (Willems and Martens, 2016). Nevertheless, although it is a widely tested theoretical model that AB occurs because of the temporal limitations of attentional resources, the mechanism of the occurrence of AB still demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Martens and Wyble (2010) proposed that the relationship between T1 and T2 during the AB period suggests a temporal limit for reallocating attentional resources from T1 to T2. Since AB reflects temporal VSA limitations, an AB test is typically used to examine temporal VSA (Green and Bavelier, 2003;Marois and Ivanoff, 2005;Martens et al, 2006b;Dux and Marois, 2009;Willems and Martens, 2016). Although the useful field of view and AB tasks may utilize shared attentional resources, they may be related to different underlying attentional mechanisms, with spatial VSA operating at an early (perpetual) level of processing and temporal VSA operating only after perception is complete, therefore reflecting a responserelated (post-perceptual) level of processing (Vogel et al, 1998;Griffin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Only recently has it been demonstrated that AB is not as universal of a cognitive limitation as once was thought, but that it greatly differs between individuals, or groups of individuals, and these differences in the AB frequency are dependent on various factors, such as stimulus category, duration, and modality (Willems and Martens, 2016). Previous studies also illustrated that certain visual stimuli, such as faces (Awh et al, 2004;Landau and Bentin, 2008), which constitute an expertise object for almost all of us, and other expertise objects (e.g., cars for car experts, Blacker and Curby, 2016) can lower one's susceptibility to the AB effects.…”
Section: Introductionmentioning
confidence: 98%
“…Considering the AB literature, interaction of WM and the AB has been demonstrated behaviorally (e.g., Akyürek et al, 2007) and with brain imaging techniques (e.g., Johnston et al, 2012). Moreover, individuals with higher levels of WM functioning and broad attentional focus seem to perform better in the AB paradigm compared to those with lower WM and with narrow attentional focus (for a review see Willems and Martens, 2016). There are some documentations in the literature which may indicate better deployment of attention in time among musicians than non-musicians.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis put on strategy by our model could explain previous findings in the AB literature that have proven difficult to explain. This includes the effect of instructions as well as the existence of non‐blinkers (individuals who do not show an AB; Martens, Munneke, Smid, & Johnson, 2006; Willems & Martens, 2016; Willems, Wierda, van Viegen, & Martens, 2013), and the reduction of AB magnitude because of training (Choi, Chang, Shibata, Sasaki, & Watanabe, 2012). All these effects could be explained by the type of consolidation strategy.…”
Section: Discussionmentioning
confidence: 99%